Thrombolytic Failure With Streptokinase In Acute St Elevation Myocardial Infarction Using Electrocardiogram Criteria At Coronary Care Unit Of Chittagong Medical College Hospital - Rahman, Azizur; Chowdhury, Md Ibrahim; Rouf, Md Abdur; Murshed, AKM Manzur; Ryhan Uddin, Abdul Ahad Mohammed; Khan, Munir Ahsan; Karim, ASM Ahsanul; Jabed, Syed Md (Journal of Chittagong Medical College Teachers’ Association, 2014)
Thrombolysis is the commonest modality of revascularization and Streptokinase is the most widely used thrombolytic agent in Bangladesh. The thrombolytic efficacy of streptokinase has been found to be low ( 50-60%) in various international studies and its efficacy in our population requires to be investigated. ST-segment resolution 90 minutes after thrombolysis is an excellent marker of successful myocardial reperfusion having good sensitivity and specificity and thus can be used as an effective tool to determine reperfusion success. This study aimed to determine the thrombolytic failure with streptokinase in acute ST elevation myocardial infarction using 90 minute ST resolution on electrocardiogram and to compare the failure rate in this study with that found in other studies. This cross sectional observational study was conducted amongst the patients admitted in the coronary care unit (CCU) at Chittagong Medical College Hospital (CMCH) during September 2011 to February 2012. An ECG was performed at admission and 90 minutes after starting streptokinase infusion. Thrombolytic failure with streptokinase was defined using electrocardiogram criteria of less than 50 percent reduction in ST elevation in the worst infarct lead after 90 minutes of streptokinase infusion. Univariate analysis was used to test association of clinical variables with study outcome. A total of 82 patients (82 percent) failed thrombolysis using streptokinase. The failures were associated with four variables in univariate analysis model including anterior location of myocardial infarct (p-value < 0.001), longer symptom onset-to-needle time (p-value is 0.02), hypertension (p-value is 0.03) and diabetes (p-value is 0.03). Failure rates were higher compared to four international trials (GUSTO-1- 46%, Chen et al76%, Lee et al-56.8%, Riffat Sultana et al-38.5%). The failure rate was higher compared to that found in some of the international studies done both in Asian and western population which could be due to higher prevalence of streptococcal infection and hence anti-streptococcal antibody in our population. This group of patients may benefit from other early reperfusion strategy like recombinant tissue plasminogen activator (tPA) or primary PCI within 1 to 2 hours. JCMCTA 2013 ; 24 (2): 30-35